2021
DOI: 10.1039/d0ta12441a
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectrification of nanocomposites using identical polymer matrixes with different concentrations of nanoparticle fillers

Abstract: In this study, we investigate triboelectrification in polymer-based nanocomposites using identical polymer matrixes containing different concentrations of nanoparticles (NPs). The triboelectric surface charge density on polymer layers increased as the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 31 publications
0
25
1
Order By: Relevance
“…This measurement is contrary to many theories of triboelectric charging that predict no measurable charge transfer when two identical polymers are contact-separated . This is a clear indication of material transfer and heterolytic bond cleavage …”
Section: Results and Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…This measurement is contrary to many theories of triboelectric charging that predict no measurable charge transfer when two identical polymers are contact-separated . This is a clear indication of material transfer and heterolytic bond cleavage …”
Section: Results and Discussioncontrasting
confidence: 85%
“…37 This is a clear indication of material transfer and heterolytic bond cleavage. 38 Statistical analysis using a logistic regression model (see the Experimental Section for full details) 39 revealed a strong correlation between CED (polymer A) [98%] and CED (polymer B) [99%] with the sign (positive or negative) of the measured surface charge (Table S5). When this analysis was applied as a training set for simple machine learning, the test data were predicted with a ∼77% accuracy (Table S6).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that surface roughness is one of the most important factors influencing the output signals of TENGs. Lower surface roughness would have a smaller effective contact area and a low deformation level and therefore could generate less surface charge density during contacting and relaxing. Therefore, such decreased V OC and I SC observed for composite films with high BT amounts are likely originated from a reduced surface contact area as supported by SEM and AFM analyses. The above characterization results indicate that the 7BT/porous composite film is the best compromise; therefore, the highest TENG output performance is observed.…”
Section: Resultsmentioning
confidence: 95%
“…Here, the enhancement is attributed to the adsorption of the HKUST-1 to water molecules, which impacts both the electron-trapping and the dielectric constant. These select studies demonstrated that the introduction of additives into the PDMS matrix, or onto the PDMS surface, can significantly enhance the electric performance of TEGs by increasing the bulk dielectric constant or promoting charging on the contact surfaces …”
Section: Fundamentals Of Tegsmentioning
confidence: 99%